Catalytic Asymmetric Approach to the Naturally Occurring Clavine Alkaloid (+)-Lysergine - Das, Mrinal K.; Shaw, Kundan; Chaudhuri, Saikat; Mondal, Debabrata; Bisai, Alakesh (Synthesis, 2024)
An efficient asymmetric approach to the ergot alkaloids has been achieved via a highly regioselective Heck cyclization. Asymmetric induction of the key intermediate was achieved via a catalytic enantioselective α-aminoxylation catalyzed by d-proline (98% ee). Utilizing the aforementioned strategy, formal total synthesis of the ergot alkaloids (+)-lysergine and (+)-isolysergine has been achieved. Importantly, an asymmetric approach to the unnatural analogues (–)-lysergine and (–)-isolysergine has also been achieved via catalytic enantioselective α-aminoxylation using l-proline.
Keywords: asymmetric total synthesis; regioselective Heck cyclization; lysergine; α-aminoxylation; ergot alkaloids